c=√d/ab ,make d the subject.

3 answers

c=√d/ab
abc = √d
(abc)^2 = d
c=√d/ab
abc = √d
(abc)^2 = d
if i take d as subject then
d=(abc)^2
d={√d }^2(given abc = √d)
d=d or
d=(abc)^2
d=(ab√d/ab)^2
d=(ab)2(√d/ab)^2
d=d
c=√d/ab
abc = √d take bothsides sqare
(abc)^2 = d
Similar Questions
  1. How does an informational text inform an audience about a subject?(1 point)Responses by changing word choice to make the subject
    1. answers icon 11 answers
  2. Match the lack of subject-verb agreement solution to the correctlack of subject-verb agreement problem: A compound subject that
    1. answers icon 1 answer
  3. Match the lack of subject-verb agreement solution to the correctlack of subject-verb agreement problem: A compound subject that
    1. answers icon 1 answer
  4. Match the lack of subject-verb agreement solution to the correctlack of subject-verb agreement problem: A subject that is
    1. answers icon 1 answer
more similar questions